Analisis Framing Berita Metro Tv (Studi Kasus : Netralitas Presiden Joko Widodo Dalam Pemilihan Calon Presiden 2024-2029 Di Indonesia) - Fatra, Emil; Manguma, Thiara Tri (Komunika : Jurnal Ilmiah Komunikasi, 2024)
Media is the main weapon in distributing news or information to the public, especially the emergence of variations and new models from mainstream media to the new media era (social media, online). This study aims to determine Jokowi's framing in his neutrality as President in the presidential election through the Contraversi Talk Show broadcast by Metro TV. Using qualitative methods and framing analysis in producing research data. The results of this study indicate that as the attitude of the Head of State, President Joko Widodo does not show and reflect his neutrality among the three Indonesian presidential candidates. Metro TV in some of its news has framed and broadcasted political gestures from a president Joko Widodo who tends to side with a particular pair. The conclusion in this study is that President Joko Widodo openly supports and provides political direction to choose presidential candidate number 2, namely Parowo-Gibran. The implications of this study are expected to be new literacy in media and political communication research. Therefore, the researcher analyzes this study in detail as new information.